Measuring total labour productivity in the open economy: A proposal - Brondino, Gabriel; Fora Alcalde, Facund; Casaú Guirao, Miguel Ángel (PSL Quarterly Review, 2024)
In the classical approach, one of the main measures of productivity is the so-called 'total labour productivity' (TLP), which can be computed as the reciprocal of the vertically integrated labour required to produce one unit of net output. In closed economies, this index changes exclusively due to technical progress. However, in open economies, where intermediate imports are required for the production of national output, changes in TLP may reflect changes in sourcing practices, which do not necessarily represent technical progress but rather the reorganization of production chains. To account for these new sources of productivity, Pasinetti proposed considering the quantity of domestic labour embedded in exports that is employed to finance imports. Building on this idea, this paper develops an 'adjusted' measure of TLP that corrects the effect of imports on productivity and studies its properties. We compare this measure to other indices related to TLP and highlight its relevance for empirical analysis.